Сутність провадження у сфері управлінської діяльності органів виконавчої влади - Дніпров, О.; Dniprov, O. (СНУ ім. Лесі Українки, 2018)
Стаття присвячена дослідженню поняття та змісту провадження у сфері управлінської діяльності, а також його нормативно-правових засад. Розглянуто управлінські процедури державного управління, що виступають базовим елементом всього процесу регулюючого впливу. З’ясовано, що провадження у сфері управлінської діяльності як форма реалізації організаційної функції управління виступає і як засіб, і як форма управлінської діяльності. The article deals with the study of the concept of proceeding and its content features in the field of management activities, including its legal and regulatory framework. The author places importance on the management procedures in the state administration and analyzes them as a basic element of the whole process of regulative influence. The content of the regulatory and legal framework of proceeding in the administrative activity includes the following features: the subject of the proceeding are the cases related to the satisfaction of the legitimate interests of individuals or legal entities, arising mainly on the initiatives of such persons; the coercive measures are not applied in the course of carrying out administrative and procedural activities; the procedure is initiated by the executive authorities in the sphere of state administration; the procedural process is regulated and consists of several stages; management administrative procedures are realized in accordance with the administrative procedural rules; the legal evaluation of the behavior of the participants in the administrative-legal relationships is usually not conducted in the course of procedural activities. The author argues that the existing model of normative legal regulation of proceeding in the sphere of management activities should be defined as fragmentary, since the procedural rules are not general but are formulated in relation to the specific administrative actions of various authorities and their officials.
Features of Proceeding in the Management Activities of the Executive Power Bodies
Keywords: управлінська діяльність; органи виконавчої влади; провадження; адміністративна процедура; administrative activity; executive bodies; proceeding; administrative procedure